(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Deputies heard information on the parliamentary request sent to the minister of Agriculture and water resources of the Republic of Uzbekistan on the initiative of the faction of the Social-Democratic Party “Adalat”on the issue “on the status of use of water-saving technologies in Uzbekistan and prospects for increasing its efficiency, introduction of modern techniques and technologies in agricultural enterprises”.